In Vitro Characterisation of Two Naturally Occurring Mutations in the Thrombin-sensitive Region of Anticoagulant Protein S - Giri, Tusar K.; de Frutos, Pablo García; Yamazaki, Tomio; Villoutreix, Bruno O.; Dahlbäck, Björn (Thrombosis and Haemostasis, 1999)
The molecular consequences of two naturally occurring mutations in the thrombin-sensitive region of protein S were investigated using a combination of recombinant protein expression, functional analysis and molecular modelling. Both mutations (R49H and R70S) have been found in thrombosis patients diagnosed as having type I protein S deficiency. Molecular modelling analysis suggested the R49H substitution not to disrupt the structure of thrombin-sensitive region, whereas the R70S substitution could affect the 3D structure mildly. To elucidate the molecular consequences of these substitutions experimentally, site directed mutagenesis of protein S cDNA and expression in mammalian cells created the two mutants. The secretion profiles and functional anticoagulant activities of the protein S mutants were characterised. Secretion of the R49H mutant was similar to that of wild type protein S, whereas the R70S mutant showed moderately decreased expression. Neither of the mutants showed any major functional defects as cofactors to activated protein C (APC) in an APTT-based assay or in degradation of factor Va. However, both mutants demonstrated decreased activity in a factor VIIIa degradation assay, which in addition to APC and protein S also included factor V as synergistic APC cofactor. In conclusion, the R49H substitution did not produce a quantitative abnormality in vitro, raising doubts as to whether it caused the type I deficiency. In contrast, the experimental data obtained for the R70S mutant agrees well with the observed type I deficiency. Our study illustrates that in vitro experimental characterisation together with computer-based structural analysis are useful tools in the analysis of the relationship between naturally occurring mutations and clinical phenotypes.
Keywords: Anticoagulant protein S; thrombin-sensitive region; natural mutations; in vitro characterisation